Analisis Minat Beli Masyarakat Antara Jagung Manis Dan Jagung Biasa Di Pasar Tradisional Harian Kabupaten Rejang Lebong - Mya Novita Sari (University of Prof. Dr. Hazairin, SH, 2017)
This study aims to determine the effect of price on buying interest, trends and percentage percentage of differences in buying interest of people to sweet corn and corn in Rejang Lebong regency. By using Chi Square Analysis method (X2) One Sample has been found Chi squared count value = 72.028 with trust level of 0.05 or 5% then Chi Square count bigger than at Chi Square mean = 3,481 hence this mean result of research show that society in Rejang Lebong regency keeps buying sweet corn even though its price is more expensive. While the tendency of interest of corn consumer community by using Run Test analysis. Price Z arithmetic 2,199 then the price of z in table XIV = 0.0122 this price is smaller than the Î± price set at 5% or 0.05 (0.0122 <0.05) which means people's buying interest is not the same between sweet corn and maize (the order is not random). With the percentage of sweet corn of 64.92%, while the percentage of maize common by 35.08% can be interpreted that the enthusiast of sweet corn is greater or higher when compared with ordinary corn.